(untitled) (International Journal of Physiotherapy, 2014)
Background: Stroke is one of the most common neurological diseases that lead to disability in elderly population. Functional impairment of upper limb affects performance of activities in daily life. The primary objective of this study was to investigate and compare the effect of motor relearning program and thermal effect to improve upper limb motor function among stroke subjects. Methods: Random sampling method was used to select subjects with right middle cerebral artery stroke. Twenty subjects were included and randomly divided into three groups by using lottery method, ten in each group A and B. Group A trained with MRP and group B with thermal stimulation. The outcomes were measured by the MMAS, and STREAM scale. Result: Analysis of variance (ANOVA) used to find the significance of study parameters between the groups. Dependent t test was used to find the significance of study parameters between pre and post assessment within the group. According to the result Group A shows better improvement than group B, It shows that upper limb motor function improved significantly higher in Group A (P<0.001) when compared to Group B in MMAS and STREAM scale evaluation. Conclusion: The present study concluded that physiotherapy treatment by the use of motor relearning program and thermal stimulation are effective technique in improvement of upper limb motor function among Stroke subjects. It has also proved that motor relearning program was more effective on improvement of motor functions in upper limb among MCA Stroke subjects.